« Rome n’est plus dans Rome... » mais dans la Cour vitrée - Guillaume Crocquevieille (In Situ)
The Musée des Études of the École des Beaux-Arts in Paris is the culmination of a project which Felix Duban spent decades elaborating and which the glass roof of the central courtyard, accomplished by his successor Ernest Coquart, helped complete. It demonstrates the development of a vast collection of Antiquity-inspired plaster casts taken from the collections of the Academy since the seventeenth century, and considerably increased during the first half of the nineteenth century. In addition to its pedagogical aim, this display marked by the influence the great collections of antiquities in Rome is a kind of aesthetic manifesto, both in the choice of the antiques, and in its museographic principles. Given that this museography is organically linked to the architecture of the courtyard and to the neoclassical aesthetics of the École des Beaux-Arts, it only changed sporadically until 1970, when the the collections were transferred to the Petite Écurie du roi at Versailles in order to preserve this heritage.